2019
DOI: 10.22214/ijraset.2019.9008
|View full text |Cite
|
Sign up to set email alerts
|

Durability and Strength Analysis of Cement Treated Soils for Sub-Base and Base Layers of Pavement

Abstract: The development and growth in economy of the country is primarily depended on the connectivity within the country and region around. The basic and most utilized for of transportation used is the roadways and highways transportation. Good quality metal aggregate is required in large quantity for construction of roads which is scarce in nature. One alternative to this problem is to use the locally available soil by stabilising it with help of cementitious material so that it can be effectively used. The strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It should be noted that this strategy brings pavement quality while saving money, essential for less developed states economies (Jordaan & Steyn, 2021). Sharma, Bhardwaj, and Nagar (2019) provide a discourse on the economic aspect of implementing cement-treated base in flexible paving thus, offering insight on an economical approach to highly sophisticated pavement technology. In this regard, AI is one of the most important factors that can facilitate more accurate predictions of pavement life cycle and maintenance requirements.…”
Section: Analysis Of Ai's Impact On Pavement Engineeringmentioning
confidence: 99%
“…It should be noted that this strategy brings pavement quality while saving money, essential for less developed states economies (Jordaan & Steyn, 2021). Sharma, Bhardwaj, and Nagar (2019) provide a discourse on the economic aspect of implementing cement-treated base in flexible paving thus, offering insight on an economical approach to highly sophisticated pavement technology. In this regard, AI is one of the most important factors that can facilitate more accurate predictions of pavement life cycle and maintenance requirements.…”
Section: Analysis Of Ai's Impact On Pavement Engineeringmentioning
confidence: 99%
“…3) Sharma H. 1 , Bhardwaj H 2 ,. & Nagar, D 3. (2019) "Economic Analysis of use of Cement Treated Base & Sub-Base in FlexiblePavement": Cement treated flexible pavement layer require less thickness as compared to conventional pavement because the loads are distributed over a large area.…”
mentioning
confidence: 99%
“…1 , Sharma S 2 ,. & Sachdeva S. N 3. (2018) in their study "Thickness Reduction in Flexible Pavement Using Cement Treated Base and Sub-Base" observed that use of CTB and CTSB saves the material cost, transportation cost, maintenance cost.…”
mentioning
confidence: 99%